Modern treatment methods in atopic dermatitis - literature overview - Borowska-Łygan, Martyna; Tomaszewski, Jakub; Urban, Wojciech; Strużek, Konrad; Biłogras, Jan; Karamus, Kornelia; Rejmak, Rafał Wojciech (Journal of Education, Health and Sport, 2025)
Introduction and aim: Atopic dermatitis (AD) is a chronic inflammatory skin disease. It is characterised by periods of exacerbation and remission of symptoms such as pruritus, dry skin and eczematous lesions with characteristic morphology. The aim of this study is to present the current state of knowledge on new treatments for atopic dermatitis. Review methods: The review was based on publicly available PubMed and Google Scholar databases from 2020 to 2024 using the following phrases: atopic dermatitis, treatment of atopic dermatitis, diagnosis of atopic dermatitis, epidemiology, biological treatment of atopic dermatitis, JAK inhibitors, stem cells, dermatitis. Brief description of the state of the art: Atopic dermatitis is a disease whose mechanism of origin is incompletely understood.It involves interactions between genotype, environment, and the immune system, and is largely related to the T-cell response. The main symptom is pruritus and dry skin leading to lichenification or exfoliation of the epidermis, which characterise the chronic form. Diagnosis is confirmed by clinical criteria such as skin lesions characteristic of AD, a family predisposition to allergic disease and a full history and skin tests. Treatment focuses on managing the symptoms associated with the disease and improving the patient's quality of life using mainly corticosteroids, calcineurin inhibitors and antihistamines. Recent studies show positive effects of treatment with biologic drugs, JAK inhibitors, stem cells and provide great hope towards the development of treatments for atopic dermatitis. Summary: The authors emphasise the need for further research towards the development of promising, innovative treatments for atopic dermatitis in order to significantly improve patients' quality of life.